2018
DOI: 10.1002/app.46212
|View full text |Cite
|
Sign up to set email alerts
|

Acrylated epoxidized soybean oil as a styrene replacement in a dicyclopentadiene‐modified unsaturated polyester resin

Abstract: Nonvolatile and nonhazardous acrylated epoxidized soybean oil (AESO) was investigated as a replacement for hazardous styrene in a commercial unsaturated polyester (UPE) resin [a mixture of styrene and a dicyclopentadiene (DCPD)‐modified UPE (DCPD–UPE)]. DCPD–UPE was prepared from ethylene glycol, diethylene glycol, maleic anhydride, and DCPD. Mixtures of AESO and DCPD–UPE [AESO–(DCPD–UPE) resins] were found to be homogeneous, easily pourable solutions at room temperature. The glass‐fiber‐reinforced composites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…Similar results were obtained within the scope of the study conducted by Wu and Li (2018). The data presented showed that the AESO additive ratio exceeding 50 wt% leads to a significant decrease in bending properties for composites as well as other mechanical properties [51]. The flexural strength of the composites including 0-40 wt% AESO content shows 200-540 MPa which is higher than the flexural strength of pure epoxy resin (118 MPa [49]) stated in the literature indicating the positive effect of introducing jute fabric as reinforcement material and the AESO resin up to a limit (40 wt%).…”
Section: Three-point Bending Testsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were obtained within the scope of the study conducted by Wu and Li (2018). The data presented showed that the AESO additive ratio exceeding 50 wt% leads to a significant decrease in bending properties for composites as well as other mechanical properties [51]. The flexural strength of the composites including 0-40 wt% AESO content shows 200-540 MPa which is higher than the flexural strength of pure epoxy resin (118 MPa [49]) stated in the literature indicating the positive effect of introducing jute fabric as reinforcement material and the AESO resin up to a limit (40 wt%).…”
Section: Three-point Bending Testsupporting
confidence: 88%
“…In a study of Liu et al (2019), the lowest flexural strength was achieved for pure AESO resin with the highest flexural strain, which was resulted from its low crosslinking density and long molecular chains of AESO [34]. Similar results were obtained within the scope of the study conducted by Wu and Li (2018). The data presented showed that the AESO additive ratio exceeding 50 wt% leads to a significant decrease in bending properties for composites as well as other mechanical properties [51].…”
Section: Three-point Bending Testsupporting
confidence: 68%
“…Consequently, the crosslinking density and interfacial reaction between reinforcement and the matrix can be improved significantly, leading to the enhancement of storage modulus, Tg and water resistance. As a nonvolatile and nonhazardous chemical, AESO is a suitable replacement for styrene in unsaturated polyester (UPE) resin to obtain hybrid polymer networks [90][91][92][93][94]. The UPE with unsaturated sites works as the co-monomer for AESO, and the final products usually exhibit comparable properties to correspondingly styrene-based products.…”
Section: Thermal Initiation Of Aesomentioning
confidence: 99%
“…In another study, phosphorylated polyols derived from the CSO were used to synthesize waterborne polyurethane dispersions . Li and coworkers have reported the possibility of using commercially available acrylated epoxidized soybean oil (ESO) as a styrene alternative and diluent to facilitate the processing of unsaturated polyester for the production of fiber‐reinforced composites . Several studies have also reported synthesis of biobased resin by using commercially available ESO reacted with maleic anhydride.…”
Section: Introductionmentioning
confidence: 99%